The video studio - Bermingham, Alan; Talbot-Smith, Michael; Angold-Stephens, Ken; Boyce, Ed (Media manuals (Routledge), 2016)
The recent demise of the independent television companies and the expansion of satellite and cable networks has led to an explosion in small, independent production facilities. In parallel with this development has been a steady increase in media training and a major expansion in corporate video facilities. The Video Studio is written for everyone contemplating setting-up a professional installation, whether studio or location based. The Video Studio shows how to estimate the scale of investment required and, depending on the nature and frequency of use of the facility, the layout of technical areas and the function of the main items of equipment is described in easy to understand language. In short this is a nuts and bolts approach to planning and operating a studio of 150 square metres or less. Completely updated to take account of all the recent technological advances which have taken place, the book now covers: DAT, timecode, digital compression, non-linear editing and all current digital video formats.